KICHIK TADBIRKORLIKNING HUDUDLARNING IJTIMOIYIQTISODIY RIVOJLANISHIGA TA’SIRI VA UNING EKONOMETRIK TAHLILI (UBS Scientific Bulletin, 2025)
This article presents the impact of small business in our countryon the socio-economic development of regions and its econometric analysis. Theanalysis was carried out using the method of least squares.